KESANTUNAN BERBAHASA PADA KOMENTAR NETIZEN DALAM KASUS PERUNDUNGAN TIMOTY KAJIAN TEORY GEOFFREY LEECH : PENELITIAN SKRIPSI - Putri, Kristina Ananda; Susilawati, Lis; Muliyono , Nurwakhid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the rampant phenomenon of bullying on social media which has elicit various responses from netizens, especially in the case of Timothy's bullying on the TikTok application. The formulation of the problem in this study is how to apply the maxim of sympathy in the comments of netizens on the case of Timothy's bullying on TikTok, and how the form of the application of the maxim of wisdom in the comments of netizens on the bullying case. The purpose of this study is to describe the form of politeness in language that contains the maxim of sympathy and to describe the application of the maxim of wisdom in netizens' comments related to the case. This study uses a qualitative descriptive method with a pragmatic approach, especially Geoffrey Leech's theory of politeness. Data in the form of netizens' comments on video uploads related to Timothy's bullying case on TikTok were then analyzed to identify the application of the two maxims in detail and contextually through linguistic interpretation. The results of the study show that the maxim of sympathy arises through the expression of empathy, condolence, prayer, and affirmation of human values. Netizens try to maximize moral support to victims and families through subtle, caring, and emotionally meaningful language. Meanwhile, the maxim of wisdom is seen through comments containing advice, invitations to respect each other, polite criticism, encouragement for educational institutions to act fairly, and moral reflection on the importance of maintaining speech and behavior on social media. The comments that have emerged show a collective awareness that speech has an impact on a person's psychological wellbeing. This study confirms that in the midst of the rise of hate speech, netizens still show politeness in language by placing empathy, care, and humanity as the basis for communication. This proves that the maxim of sympathy and the maxim of wisdom play an important role in creating a positive and harmonious digital space for users.